2018
DOI: 10.1007/s00418-018-1692-7
|View full text |Cite
|
Sign up to set email alerts
|

Oct-4 and CD44 in epithelial stem cells like of benign odontogenic lesions

Abstract: Benign epithelial odontogenic lesions are great clinical importance entities that develop in the jaws from the tissues that form teeth. It has been shown that benign and malignant tumors are present in a large number of tumor stem cells, which has great implications in the development of these lesions. Oct-4 and CD44 have been demonstrated as important markers for tumoral stem cells. The aim of this study was investigate the presence of stem cell markers Oct-4 and CD44 in benign epithelial odontogenic lesions.… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
21
0
1

Year Published

2019
2019
2025
2025

Publication Types

Select...
8
2

Relationship

1
9

Authors

Journals

citations
Cited by 16 publications
(23 citation statements)
references
References 42 publications
0
21
0
1
Order By: Relevance
“…The expression of Oct4, known to play a critical role in the development and self‐renewal of embryonal stem cells and in the invasiveness and chemoresistance of certain cancers, 38 has been found to be negative in the present study. Previous works, in which Oct4 has been examined in the epithelial component of odontogenic lesions, reported equivocal expression, ranging from negative in AMB, DC, and OKC, 14,15 through scarcely positive in radicular cysts 14 and to definitely positive in AMB and OKC, 16,39 and in AOT and ameloblastic carcinoma 14 . In other types of tumors, it has been shown that stem cell markers, such as Nanog and SOX2, were differentially expressed in the epithelial and stromal components 4 and that the relative frequency of these cells was tissue‐related 40 .…”
Section: Discussionmentioning
confidence: 95%
“…The expression of Oct4, known to play a critical role in the development and self‐renewal of embryonal stem cells and in the invasiveness and chemoresistance of certain cancers, 38 has been found to be negative in the present study. Previous works, in which Oct4 has been examined in the epithelial component of odontogenic lesions, reported equivocal expression, ranging from negative in AMB, DC, and OKC, 14,15 through scarcely positive in radicular cysts 14 and to definitely positive in AMB and OKC, 16,39 and in AOT and ameloblastic carcinoma 14 . In other types of tumors, it has been shown that stem cell markers, such as Nanog and SOX2, were differentially expressed in the epithelial and stromal components 4 and that the relative frequency of these cells was tissue‐related 40 .…”
Section: Discussionmentioning
confidence: 95%
“…Further studies observed the stem cell indicators in both the stellate reticulum like cells and the peripheral basal cells of ABs (22,23). A recent study performed by Monroy et al (23), demonstrated a high expression of a tumor stem cell marker, namely Oct-4 in the suprabasal layers of OKC and in both stellate reticulum and peripheral columnar cells of AB, while the CD44, which is another stem cell marker used in the same study was highly expressed in all epithelium of OKC and AB (23).…”
Section: Discussionmentioning
confidence: 96%
“…A series of studies have shown that rodent incisors grow continuously throughout life owing to the epithelial progenitor cells in the cervical loop, an area where the inner and the outer enamel epithelium meet at the rim of the enamel organ at bell stage (12)(13)(14). Moreover, stem cell markers such as Oct-4, CD44 and K15 have been demonstrated in odontogenic lesions (15,16). Evidences above suggest the possibility that there are stem cells in the capsule of DC.…”
Section: Introductionmentioning
confidence: 99%